Pragmatics, Discourse and Society, Volume 1 A Festschrift for Akin Odebunmi. - Osunbade, Niyi; Unuabonah, Foluke; Osisanwo, Ayo (Cambridge Scholars Publisher, 2021)
This two-volume work speaks to the entire scope of Professor Odebunmi's research concerns in general pragmatics, medical and clinical pragmatics, literary discourse, critical discourse analysis, applied linguistics and language sociology. Its 52 chapters across both volumes (24 chapters in this volume and 28 chapters in Volume 2) written by established scholars such as Jacob Mey, Paul Hopper, Joyce Mathangwane, and Ming-Yu Tseng, in addition to the honoree, explore the dynamics of the interplay of spatial, temporal, agential and (non-)institutional factors that drive discourse/textual construc.